Teachers, Pedagogues and Trade Unionists. the Communists in the Sarmiento School. Argentina 1918-1943 - Alvarez-Vallejos, R; Matamoros-Fernandez, C (HIPATIA PRESS, 2020)
The objective of this article is to characterize the experience developed by the Argentine communist teachers during the years 1918-1943 in their political ideological, educational and union aspects. A part of the historiography has highlighted the debts of these teachers with mechanistic positivism, those that their canonical text would have had in the work of Anibal Ponce Education and class struggle. Thus, they would have rejected all kinds of pedagogical renewal associated with the New School movement, rescuing instead the ideas of liberalism defended by Domingo Faustino Sarmiento. From the analysis of the texts of the communist pedagogues, their educational experiences and their union participation, we seek to explain how these educators did develop renovating experiences in education, but not associated with ideal looks of the school, but from a vision of society, and the school, dyed by the class struggle.